2020
DOI: 10.3389/fendo.2020.00291
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Variability Increases Dementia Risk Among Older Adults: A Nationwide Population-Based Cohort Study

Abstract: Background: Recent growing evidences suggest that body weight (Bwt) variability, a repeated loss and regain of weight within a specific period, causes metabolic disturbances and can be a marker for poor homeostasis. Although there have been many studies about the association between Bwt variability and various health status, its association with the incidence of dementia among elderly people has not been examined. Methods: We performed a retrospective elderly cohort study from 19,987 participants with mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…To our knowledge, there are very few studies, which investigated the association between body weight variability and risk for dementia. Previous studies reported that higher weight variability was associated with an increased risk for dementia 15,16 . In our study, we used ASV, the average absolute difference between BMI values of each measurement, as a measure of variability.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, there are very few studies, which investigated the association between body weight variability and risk for dementia. Previous studies reported that higher weight variability was associated with an increased risk for dementia 15,16 . In our study, we used ASV, the average absolute difference between BMI values of each measurement, as a measure of variability.…”
Section: Discussionmentioning
confidence: 96%
“…Research examining the association between anthropometric parameter variability and cognitive function in the general older population is scarce. Only one prospective study has examined the association between BMI variability and dementia [39], and others are limited to the effect of body weight variability on dementia [40][41][42]. In our study, we examined the relationship between the variability in two obesity indicators (BMI and WHtR) and cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Future research on the role of BMI in memory loss has not yet provided a definitive picture. Certain studies have shown no correlation or even reduced BMI with dementia or Alzheimer’s disease (AD) [ 3 , 4 ], whereas others have indicated higher BMI as a possible cause for dementia [ 5 ], or overweight to be correlated with dementia decades later. At least partially, the dynamic interplay may explain the various findings obtained by different experiments.…”
Section: Introductionmentioning
confidence: 99%